Creating Second Lives : Community, Identity and Spatiality as Constructions of the Virtual. - Ensslin, Astrid (Taylor & Francis, 2011)
This book aims to provide insights into how 'second lives' in the sense of virtual identities and communities are constructed textually, semiotically and discursively, specifically€in the online environment Second Life and Massively Multiplayer Online Games such as World of Warcraft. The book's philosophy is multi-disciplinary and its€goal is to explore the question of how we as gamers and residents of virtual worlds construct alternative online realities in a variety of ways. Of particular significance to this endeavour are conceptions of the body in cyberspace and of spatiality, wh.